PENGEMBANGAN BAHAN AJAR MATAKULIAH MENULIS FIKSI BERBASISNILAI-NILAI PENDIDIKAN MULTIKULTURAL PADA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA IKIP BUDI UTOMO MALANG - Susandi Susandi (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2017)
The purpose of this study is to describe: (1) teaching material product; (2) the presentation; (3) the use of language; and (4) graphic writing fiction teaching materials based multicultural values.The design of the teaching materials development in this study was adapted from the theory of design R & D by Borg and Gall which is carried out through five stages: (1) preliminary study, (2) planning, (3) developing type/shape of the initial product, (4) early stage field trials and revision, (5) primary field trials and revision. Data analysis of this study is obtained percentage score (1) expert literature instructional materials of 98,9%, (2) proficient writing instructional materials 97.14%,(3) field practitioners in this case teacher of 76.67%,and (4) the students of 85.125%, which means that the percentage of product development is also quite valid/ feasible for learning offiction writing based multicultural values in the education program of language and Indonesian literature IKIP Budi Utomo Malang.